INNOVATIVE DIGITAL PEDAGOGIES IN FINE ARTS EDUCATION: ENHANCING CREATIVITY THROUGH AI-BASED LEARNING TOOLS - Olimova Mohidil Sherzod qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the integration of innovative digital pedagogies, particularly artificial intelligence (AI), in fine arts education. As digital transformation reshapes teaching and learning environments, AI-based tools provide new opportunities for creative development, personalized learning, and advanced visual analysis. This research examines how AI enhances artistic competencies, supports reflective learning, and promotes inclusive participation in creative practice. The article also highlights potential risks, ethical concerns, and pedagogical responsibilities associated with AIsupported art instruction. Findings indicate that when implemented appropriately, AI strengthens artistic thinking, expands student experimentation, and enriches overall educational experience while maintaining the integrity of traditional fine arts methods.